2017
DOI: 10.1016/j.fertnstert.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Varicoceles: prevalence and pathogenesis in adult men

Abstract: Varicocele, or dilation of the pampiniform venous plexus, affects up to 15% of men. However, few of these men encounter problems with fertility. This discrepancy between men with varicocele and the number of adversely affected men has led to abundant research to identify the mechanisms for formation of varicocele as well as the pathologic mechanisms by which varicoceles affect fertility potential. In this review, we discuss the prevalence of varicocele in adults, the anatomic features of varicocele, the leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 72 publications
0
64
0
1
Order By: Relevance
“…Indirectly, it is known that the vasodilation effect of nitric oxide increases the blood flow in the blood vessels of various body tissues, including the testes (Casey, Walker, Ranadive, Taylor, & Joyner, ; Simmonds, Detterich, & Connes, ). Increased blood flow in the testes was found to enhance testosterone production by Leydig cells, which may enhance spermatogenesis in Sertoli cells (Clavijo, Carrasquillo, & Ramasamy, ; Wang, Gu, Tao, & Wu, ), and consequently improves semen quality.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Indirectly, it is known that the vasodilation effect of nitric oxide increases the blood flow in the blood vessels of various body tissues, including the testes (Casey, Walker, Ranadive, Taylor, & Joyner, ; Simmonds, Detterich, & Connes, ). Increased blood flow in the testes was found to enhance testosterone production by Leydig cells, which may enhance spermatogenesis in Sertoli cells (Clavijo, Carrasquillo, & Ramasamy, ; Wang, Gu, Tao, & Wu, ), and consequently improves semen quality.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Genitourinary infection, urological surgery during childhood, and illicit drugs are common and under-recognised causes of male infertility. Varicoceles increase scrotal temperature and reduce testicular perfusion 6. A meta-analysis of observational studies noted that varicoceles were associated with reduced sperm quality 7.…”
Section: What Causes Male Infertility?mentioning
confidence: 99%
“…Varicocele is defined as an abnormal dilation of the pampiniform plexus, the drainage complex in testis. This physical alteration can result in blood stasis, heat stress and retrograde flow of metabolites, and this is particularly important for smokers, because the toxic metabolites present in cigarettes can cross the blood testis/epidydimis barrier, altering its milieu (Benoff, Millan, Hurley, Napolitano, & Marmar, 2004; Clavijo, Carrasquillo, & Ramasamy, 2017; El Mulla, Köhn, El Beheiry, & Schill, 1995; Masson & Brannigan, 2014). Previous studies have demonstrated that varicocele potentiate the toxic effects of smoking (Benoff et al, 2004; El Mulla et al, 1995), but this literature still needs more studies.…”
Section: Introductionmentioning
confidence: 99%